Synthesis and characterization of Mn0.5Zn0.5Fe2O4 and Fe3O4 nanoparticle ferrofluids for thermo-electric conversion - Sansom, Christopher L.; Jones, Paul M.; Dorey, Robert A.; Beck, C.; Stanhope-Bosumpim, A.; Peterson, J. (Elsevier Science B.V., Amsterdam., 2013)
Ferrofluids containing nanoparticles of Mn0.5Zn0.5Fe2O4 (MZ5) and Fe3O4 (magnetite) have been examined as potential thermal transport media and energy harvesting materials. The ferrofluids were synthesized by chemical co-precipitation and characterized by EDX to determine composition and by TEM to determine particle size and agglomeration. A range of particle coatings and carrier fluids were used to complete the fluid preparation. Commercially available ferrofluids were tested in custom built rigs to demonstrate both thermal pumping (for waste heat removal applications) and power induction (for power conversion and energy harvesting applications). The results indicate that simple ferrofluids possess the necessary properties to remove waste heat, either into thermal storage or for conversion to electrical power.
Keywords: Ferrofluid; Heat transfer; Energy harvesting